THE EFFECT OF POWERPOINT AS INTERACTIVE MEDIA IN INCREASING VOCABULARY MASTERY OF THE SEVENTH GRADES STUDENTS - Putri, Delvia Lingga; Aruan, Rumini Rotua; Purwanti, Indah Tri (Universitas PGRI Sumatera Barat, 2025)
Students need to understand the meaning of various vocabularies that can support the learning process. With the importance of vocabulary mastery, this study aims to find out the increase in vocabulary mastery in seventh grade students from the effectiveness of PowerPoint as interactive media. This pre-experimental research used a group pretest and post-test. This test was conducted with 34 students from class 7A who were selected as samples through cluster random sampling. Based on the results obtained, the mean value of the pre-test was 60.58 and 81.67 on the post-test. Furthermore, the significance value (2-tailed) is 0.000, which is lower than 0.05. So it can be known that the effectiveness of PowerPoint as interactive media in increasing vocabulary mastery is accepted.